Assessment of childhood immunization services at private healthcare facilities in Indonesia: a case study in a highly-populated city - Suwantika, Auliya A.; Zakiyah, Neily; Abdulah, Rizky; Diantini, Ajeng (Frontiers in Public Health, 2023)
The needs to enhance the utilization of the private sector in immunization programs in Indonesia while maintaining the high quality of services provided are evident. This study aimed to rapidly assess immunization services at private healthcare facilities in Indonesia by using Bandung, the most densely populated city, as the reference case. Initially, a situation analysis was conducted by collecting data from selected healthcare facilities (n=9). Furthermore, a qualitative study was taken into account by developing framework approaches and conducting interviews with different layers, such as mid-level managers at healthcare facilities (n=9), professional organizations (n=4), and public stakeholders (n=7). The situation analysis showed that private healthcare facilities had provided sufficient time for essential childhood immunization services with adequate staff. Nevertheless, the number of limited staff the Ministry of Health (MoH) has trained remains a programmatic problem. Furthermore, private healthcare facilities have used the MoH guidelines and additional internal guidelines for immunization services as the primary reference, including in the efforts to provide complete and reliable equipment. Vaccine availability at private healthcare facilities is manageable with an acceptable level of out-of-stock. The results of our interviews highlighted three key findings: the lack of coordination across public and private sectors, the need for immunization service delivery improvement at private healthcare facilities, and the urgency to strengthen institutional capacity for advocacy and immunization systems support. Even though private healthcare facilities have been shown to have a modest contribution to childhood immunization services in Indonesia, efforts should be made to expand the role of private healthcare facilities in improving the performance of routine immunization programs.